Reattachment of Fractured Tooth Fragment with Fiber Post: A Case Series with 1-Year Followup - C. M. Sapna; R. Priya; N. B. Sreedevi; Rakesh R. Rajan; Renjith Kumar (Case Reports in Dentistry)
Coronal fractures of the anterior teeth are common sequelae of dental trauma. In case of complex fractures, where the fractured segment is available and there is close approximation of the segment to the remaining tooth, root canal treatment followed by reattachment of the fractured segment with fiber post reinforcement is a feasible option. The procedure is simple and economic and needs less chair-side time as compared to many conventional methods. In addition, the procedure provides good and long-lasting esthetics, because the original morphology, color, and surface texture are maintained. This paper reports three cases of complex coronal tooth fracture successfully managed using tooth fragment reattachment.